2022
DOI: 10.3389/fevo.2022.762146
|View full text |Cite
|
Sign up to set email alerts
|

Fat Stores and Antioxidant Capacity Affect Stopover Decisions in Three of Four Species of Migratory Passerines With Different Migration Strategies: An Experimental Approach

Abstract: During migratory stopovers, birds must make decisions about when and where to travel and these decisions are likely contingent on their fuel stores, food availability, and antioxidant capacity as well as seasonal changes in key environmental factors. We conducted a field experiment on an offshore stopover site (Block Island, Rhode Island, United States: 41°130N, 71°330W) during autumn migration to test the hypothesis that birds with greater fuel stores and non-enzymatic antioxidant capacity have shorter stopov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Migratory endurance flight increases oxidative damage [ 13 , 15 , 19 , 32 ], which again can be reduced at stopover within a matter of days, at least in case of lipid damage [ 12 , 20 , 51 ]. Restoring the oxidative balance is thought to be one of the many functions of stopover [ 37 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Migratory endurance flight increases oxidative damage [ 13 , 15 , 19 , 32 ], which again can be reduced at stopover within a matter of days, at least in case of lipid damage [ 12 , 20 , 51 ]. Restoring the oxidative balance is thought to be one of the many functions of stopover [ 37 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although we fully agree with this notion, our current results do not provide much support for this,we found no evidence for an association between migrants’ stopover departure decisions and their malondialdehyde (MDA concentration, indicative of oxidative lipid damage. In a study on temporarily caged migrants, Cooper-Mullin and McWilliams [ 12 ] found that supplementation with dietary antioxidants may decrease stopover duration (thus increasing departure probability). However, this effect was only present in one of the two study species, and then only in birds kept on a maintenance diet, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations